A high-resolution multi-scalar approach for micro-mapping historical landscapes in transition : a case study in Texas, USA (2019)
The European Landscape Convention (ELC) defines landscape as ‘an area, as perceived by people, whose character is the result of the action and interaction of natural and/or human factors’ (Council of Europe 2000: article 1). The ELC calls for states to introduce landscape in the law ‘as an essential component of people’s surroundings, an expression of the diversity of their shared cultural and natural heritage and a foundation of their identity’ (Council of Europe 2000: article 5a). As such, a landscape reflects a history of environmental, social, and cultural engagements, and it inscribes material records of human activities in places over time (David and Thomas 2008).